Rethinking Premodern Japanese Buddhist Texts: A Case Study of Prince Shōtoku’s "Sangyō-gisho" - Dennis, Mark W. (Relegere, 2011)
This article examines the Sangyō-gisho 三経義疏 (Commentaries on the Three Sūtras), three Buddhist texts written in classical Chinese that have been attributed to Japan's Prince Shōtoku (574-622 CE). I will focus on the different ways in which four figures from the Kamakura era (1185-1333 CE) understood, used, and valued these texts. Even among this small group of contemporary monks from the thirteenth century we will find distinct notions of what constitutes the "text," some of which differ in important ways from modern scholarly conceptions of the Sangyō-gisho. Through highlighting these different perspectives, I offer an alternative approach to a large body of modern scholarly studies, which has focused on a set of technical concerns looking back to the moment of the texts' composition.